Ice in Wonderland / Ahmad Saddam Dindi Albat... [et al.] - Albat, Ahmad Saddam Dindi; Kumin, Helda; Halim, Noraisah; Atan, Rashidah; Zaki, Norsyazanadia (2010)
Ice Wonderland is a brand new ice cream shop in town. It is created to give the first and foremost new leisure not only for children who loves ice cream, but also for teenager, working people and family. Ice Wonderland focus its menu obviously only on ice cream with variety types of its. Such as, we have flavors of the month, classic flavors, seasonal flavors, and regional flavors. For soft serve, we have cups and cones, soft serve sundaes and fruit cream. As for sundaes, we have premium sundaes, classic sundaes and soft serve sundaes. We also serve cakes, such as classic cakes, fudge crunch cakes, roll cakes, pies and cupcakes. As for beverages, we have shake, fruit blast, fruit blast smoothies, fruit cream, floats, freezes and soft drinks.